Sequencing and de novo assembly of the Asian clam (Corbicula fluminea) transcriptome using the Illumina GAIIx method. - Huihui Chen; Jinmiao Zha; Xuefang Liang; Jihong Bu; Miao Wang; Zijian Wang (PLoS ONE, 2013)
BACKGROUND: The Asian clam (Corbicula fluminea) is currently one of the most economically important aquatic species in China and has been used as a test organism in many environmental studies. However, the lack of genomic resources, such as sequenced genome, expressed sequence tags (ESTs) and transcriptome sequences has hindered the research on C. fluminea. Recent advances in large-scale RNA-Seq enable generation of genomic resources in a short time, and provide large expression datasets for functional genomic analysis. METHODOLOGY/PRINCIPAL FINDINGS: We used a next-generation high-throughput DNA sequencing technique with an Illumina GAIIx method to analyze the transcriptome from the whole bodies of C. fluminea. More than 62,250,336 high-quality reads were generated based on the raw data, and 134,684 unigenes with a mean length of 791 bp were assembled using the Velvet and Oases software. All of the assembly unigenes were annotated by running BLASTx and BLASTn similarity searches on the Nt, Nr, Swiss-Prot, COG and KEGG databases. In addition, the Clusters of Orthologous Groups (COGs), Gene Ontology (GO) terms and Kyoto Encyclopedia of Gene and Genome (KEGG) annotations were also assigned to each unigene transcript. To provide a preliminary verification of the assembly and annotation results, and search for potential environmental pollution biomarkers, 15 functional genes (five antioxidase genes, two cytochrome P450 genes, three GABA receptor-related genes and five heat shock protein genes) were cloned and identified. Expressions of the 15 selected genes following fluoxetine exposure confirmed that the genes are indeed linked to environmental stress. CONCLUSIONS/SIGNIFICANCE: The C. fluminea transcriptome advances the underlying molecular understanding of this freshwater clam, provides a basis for further exploration of C. fluminea as an environmental test organism and promotes further studies on other bivalve organisms.